2020
DOI: 10.1002/elan.201900717
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Tracing of Butein Using Carbon Nanoparticles Interfaced Electrode Processed from Biowaste

Abstract: Nanoparticles of carbon derivatized from pyrolysis of biowaste oil palm leaves were processed as electrochemical transducer material at the interface of glassy carbon electrode. This modified electrode exhibits convincing electron‐transfer property for voltammetric and chronoamperometric quantification of clinically important phytochemical, butein, without the use of external redox mediator and enzyme. A reversible two‐electron transfer redox property observed from butein is distinct at the electrode interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Δ E p of the BCD-Bt system was found to be 0.94 V, suggesting the transformation of the quasi-reversible redox behavior of Bt into reversible upon conjugation with BCD. The conversion of ortho dihydroxy groups into ortho quinone in the BCD-Bt implies the two-electron and two-proton reaction at the interface . To reveal the reversibility of the prepared conjugated system at the electrode interface, a scan rate dependence study was performed (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Δ E p of the BCD-Bt system was found to be 0.94 V, suggesting the transformation of the quasi-reversible redox behavior of Bt into reversible upon conjugation with BCD. The conversion of ortho dihydroxy groups into ortho quinone in the BCD-Bt implies the two-electron and two-proton reaction at the interface . To reveal the reversibility of the prepared conjugated system at the electrode interface, a scan rate dependence study was performed (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The conversion of ortho dihydroxy groups into ortho quinone in the BCD-Bt implies the two-electron and two-proton reaction at the interface. 34 To reveal the reversibility of the prepared conjugated system at the electrode interface, a scan rate dependence study was performed (Figure 3B). The corresponding linearity of the peak current is illustrated in Figure 3C, enabling a coefficient of determination value R 2 = 0.99, suggesting the surfaceconfined process at the electrode−electrolyte interface.…”
Section: Cyclic Voltammetry Of the Bcd-bt Conjugated Systemmentioning
confidence: 99%
“…10 From this viewpoint, electrocatalysis involving interfacial electron transfer at electrodes can be employed for rapid bioavonoid determination. 11 Indeed, several studies on the electrochemical detection of bioavonoids have been reported, especially using electrodes functionalized with different nanomaterials, such as gold nanocage, 12 gold nanoparticles, 13 carbon nanotubes, 14 graphene oxides, 15 carbon nanoparticles 16 and their combinations. [17][18][19][20] For example, Sebastian et al reported a amine-functionalized multi-walled carbon nanotube (CNT) and 3D rose ower-like zinc oxide nanocomposite for electrochemical detection of morin.…”
Section: Introductionmentioning
confidence: 99%
“…Such novel carbon materials can be considered for various practical applications. Different methods exist in the literature for the synthesis of carbon nanospheres. The method employed here to synthesize CNSs is eco-friendly without the usage of any catalysts and cost-effective . In the present research work, CNSs have been synthesized by a catalyst-free pyrolysis technique from the leaves of Mimosa pudica , a perennial flowering plant well-known for its nyctinastic foliar movement.…”
Section: Introductionmentioning
confidence: 99%